PERCEPTION OF INDONESIAN EFL TEACHER ON THE IMPLEMENTATION OF 2013 ENGLISH CURRICULUM - Ina Rohiyatussakinah (FKIP, Universitas Banten Jaya, 2020)
2013 Curriculum in Indonesia implemented since 2014-2015 , by the Ministry of Education and Culture of Republic of Indonesia. The reason is to build character education and improving student’s creative thinking are the main reason of the new curriculum development. research perception on the implementation of 2013 English curriculum and identified problem faced by teachers in implementing it. through qualitative design, the study was conducted at one senior high school in Serang. This study discloses EFL Indonesian Teacher perception 2013 curriculum, through interview teachers for in-depth analysis. The finding showed curriculum 2013 implemented, the teacher used specific syllabus and 3 workbook applied. Most of the teachers claim that English curriculum 2013 not easily to implemented, Difficulties in applying learning revolution, rubric of assessment, and using scientific approach to improve students English skill. The results confirm that process of 2013 curriculum from teacher perception and problem occurred by teacher. It also recommended that the teacher should put more effort on applying by joining any training, workshop and improve their creativity adapt to the advance of knowledge and technology.